2016
DOI: 10.1038/srep34183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the transcriptomes and cuticular protein gene expression of alate adult, brachypterous neotenic and adultoid reproductives of Reticulitermes labralis

Abstract: The separation of primary reproductive and secondary reproductive roles based on the differentiation of alate adults and neotenic reproductives is the most prominent characteristic of termites. To clarify the mechanism underlying this differentiation, we sequenced the transcriptomes of alate adults (ARs), brachypterous neotenics (BNs) and adultoid reproductives (ANs) from the last instar nymphs of Reticulitermes labralis. A total of 404,152,188 clean sequencing reads was obtained and 61,953 unigenes were assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…RR-2 proteins are involved in hard cuticles and the exoskeleton, which protects the insect from environmental stresses, such as biological stresses, abrasions, desiccation, and UV radiation. 17,34 As expected, AcCP19 was highly expressed in the integument, and the expression of AcCP19 increased under desiccation stress. RNAi of AcCP19 increased water loss rate and induced lethal phenotypes, including a darker color in all three aphid species.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…RR-2 proteins are involved in hard cuticles and the exoskeleton, which protects the insect from environmental stresses, such as biological stresses, abrasions, desiccation, and UV radiation. 17,34 As expected, AcCP19 was highly expressed in the integument, and the expression of AcCP19 increased under desiccation stress. RNAi of AcCP19 increased water loss rate and induced lethal phenotypes, including a darker color in all three aphid species.…”
Section: Discussionsupporting
confidence: 72%
“…Phylogenetic analysis and sequence comparisons revealed that CP19 belongs to the CPR family with a highly conserved RR‐2 motif in aphids. RR‐2 proteins are involved in hard cuticles and the exoskeleton, which protects the insect from environmental stresses, such as biological stresses, abrasions, desiccation, and UV radiation . As expected, AcCP19 was highly expressed in the integument, and the expression of AcCP19 increased under desiccation stress.…”
Section: Discussionsupporting
confidence: 65%
“…It serves as attachment site for muscles, implement sensory perceptions and coloration, also provide protection against parasites, pathogen, mechanical injury and perform other physiological functions. However, the cuticle mandatorily protects the whole body of insect and exist at all developmental stages, it also contains exceptional diversity in its mechanical and physicochemical properties to accommodate the functions of protected organs and tissues and enables for growth [3]. Thus, cuticle at different developmental stages from distinct parts of insect’s anatomy may have different characteristics, their functions based on the thickness, framework or morphology of unique layers, chemical composition and molecular connections in the cuticle [2, 4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies suggested that RR-1 proteins are related to soft and flexible endocuticle and RR-2 proteins are related to tough and hard exocuticle. At different developmental stages particular cuticular protein expression are mandatory for the formation of distinct cuticle layers that may likely contains appropriate combination of morphological, mechanical and physical properties which give mobility, protection and structural support [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation